The phrase (Kun fayakun) in the Holy Quran: Grammatical symantic study - Widda, Murtada (Al-Adab Journal, 2024)
The study aims to stand on the grammatical characteristics of the expression (Kun fayakun) in the Holy Quran in terms of determining the type of (Kana) and the (Fa) also its place in the syntax. Also seeks to know its significance through the grammatical guidance tense) Yakun). The study followed the descriptive analytical approach to address the subject, through three axes: defining the phrase (Kun fayakun) in the Holy Quran, nominative case (Yakun) and its significance, and the accusative (Yakun). The most important findings of this study: (Kana) in this context was complete, whether in the imperative or present tense. One of the most prominent features of this phrase is the fact that it predominates in four places. The accurrence  of  saying to say, then its restricted it to the five places, and directing the reading of the nominative to be based determing the type of the (Fa) ,some said it was a syndetic and others said it was an appeal , and the general indication for  that Allah Almighty tells us about any matter Allah wills, so in Allah work, not the indication the universe stopped at Allah command (Kun)then it is formed and happens, as for directing the reading of the accusative, it is sympathetic with(An yaqul) or an answer (Kun) it’s indication is that the thing is God’s command to the universe, although it is a being in Allah work, but the creatures do not know this universe except in the future. The context in which the composition was mentioned is a context that requires achievement in speech to express it’s absolute will, so that was in the shortest phrase (kun fayakun).